Pengaruh Environmental, Social, Governance Terhadap Nilai Perusahaan Pertambangan - Henoch Setyo Purnomo; Yuhertiana, Indrawati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the influence of Environmental Social Governance (ESG), profitability, and leverage on the value of mining companies listed on the Indonesia Stock Exchange (BEI) in the 2020-2023 period. Company value is measured using Tobin's Q, while the independent variables include ESG score, Return On Assets (ROA) as a proxy for profitability, and Debt to Equity Ratio (DER) as a proxy for leverage. The research method used is quantitative with a panel data regression approach. The sample consists of 19 mining companies selected through a purposive sampling method. Research data was obtained from annual reports and company sustainability reports published during the research period. The research results show that ESG and leverage do not have a significant effect on company value, while profitability has a positive and significant effect on company value. This indicates that ESG implementation has not become a primary consideration for investors in assessing companies in the mining sector, and that company debt levels have not become a primary concern in making investment decisions. It is also known that a company's ability to generate profits is an important factor for investors.